Badminton shuttlecock stability: Modelling and simulating the angular response of the turnover - Lin, C. S.; Chua, C. K.; Yeo, J. H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
Turnover of a badminton shuttlecock is the flipping motion of the shuttlecock after its initial contact with the racket. During the process, the shuttlecock experiences a large change in heading. In this article, the turnover stability of the shuttlecock is investigated through experiment and simulation. Three types of badminton shuttlecocks are experimentally evaluated: one feather shuttlecock (Li-Ning A+600) and two synthetic ones (Yonex Mavis 350 and Mizuno NS-5). The experimental results are applied to a response model that takes the form of an under-damped second-order transfer function. This angular response model is then used for the identification of the turnover parameters: the damping ratio and the time constant. The identified parameters are subsequently used as input for building a response function to predict the turnover angular behaviour of the shuttlecock. The feather shuttlecock, which has the highest damping ratio and the lowest time constant, is the shuttlecock with the best turnover stability. Finally, the simulated pitching moment components of the feather shuttlecock are evaluated.